Penerapan Metode SPI untuk Analisis Kekeringan di DAS Sombe - Lewara Kabupaten Sigi - Andiesse, V.W.; Lipu, S.; Setiawan, A.; Rustiati, N.B.; Oktavia, S.R.; Amaliah, T.; Tandiseru, I.F. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
The level of drought and wetness is a standard in estimating conditions in an area that occur in the past, present, and future. By knowing the SPI value of an area, it can be known the drought distribution map which aims to handle drought disaster mitigation and adaptation. This research aims to see how much the level of drought, wetness, and normal conditions that occur in the Sombe Lewara Watershed, Sigi Regency so that prevention can be carried out and the basis for government policy-making in the event of a drought disaster. The method used in this research is the SPI (Standardized Precipitation Index) method which is commonly used to determine the deviation of rainfall from the norm, in a period (monthly, bi-monthly, quarterly, and so on). This method is one of the analysis methods of the many techniques to obtain the existing drought index. In this study, the data used is rainfall data for 19 years (2003 - 2021) obtained from Porame Rain Station. The rainfall data is then processed to obtain the SPI value in the Sombe Lewara watershed. For the calculation of SPI, the processed rainfall data is then transferred to the gamma distribution to obtain the SPI value. SPI-1 index (1.145) with moderately wet conditions, SPI-3 (0.640) with normal conditions, SPI-6 (-0.234) with normal conditions, SPI-9 (1.578) with dry conditions, and SPI-12 (1.017) with moderately dry conditions.From 2003 - 2021, the year that experienced the worst drought conditions was in 2014 in SPI-1 with an SPI value of -3.888 (very dry). After all SPI values are averaged, the standard SPI value of the Sombe Lewara Watershed is in normal conditions with a value of 0.829.